Alternative use of soil conditioners for cotton cultivation (Research, Society and Development, 2024)
Some production environments may present low pH and high levels of Al3+, thus making this element a limiting factor in the productivity of the cotton crop, which makes it necessary to use agricultural gypsum as a soil conditioner and even shell dust as sources low-cost alternatives to improve soil chemical attributes. The objective of this work was to know the responses of the use of alternative soil conditioners with aluminum in the cotton crop. The experiment was carried out in August 2022, at Faculdades Integradas Stella Maris (FISMA). The design was completely randomized, with six treatments, namely: no use of soil conditioners, agricultural gypsum (3.0 t ha-1); golden mussel shell powder (3.0 t ha-1); snail powder (3.0 t ha-1); agricultural gypsum (1.5 t ha-1) with golden mussel shell powder (1.5 t ha-1) and agricultural gypsum (1.5 t ha-1) with snail powder (1.5 t ha-1)  and with four replications, totaling 24 plots or pots. The use of agricultural gypsum at a dose of 1.5 t ha-1 associated with golden mussel shell powder at a dose of 1.5 t ha-1 showed better responses in cotton development. The use of agricultural gypsum at a dose of 1.5 t ha-1 associated with golden mussel shell powder at a dose of 1.5 t ha-1 improves soil conditions for cultivation. The pyrolysis method at high temperatures to break the crystalline structures of mollusc shells was efficient.